Localization of an inhomogeneous Bose-Einstein condensate in a moving random potential - Alamir, Ardavan (2012)
We study the dynamics of a harmonically trapped quasi-one-dimensional Bose-Einstein condensate subjected to a moving disorder potential of finite extent. We show that, due to the inhomogeneity of the sample, only a percentage of the atoms is localized at supersonic velocities of a random potential. We find that this percentage can be sensitively increased by introducing suitable correlations in the disorder potential such as those provided by random dimers. © 2012 American Physical Society.